Synthesis of Silver Nanoparticles by Solanum trilobatum L. Aqueous Extract and Their Antibacterial Activity - Sakthiraj Aksitha (Wolters Kluwer Medknow Publications, 2024)
Solanum trilobatum L. (Solanaceae), commonly known as nightshade, has been traditionally used by various populations to treat a variety of ailments. Environment-friendly alternatives to chemical and physical procedures for the synthesis of nanomaterials have been proposed. In this research, the hot plate combustion method is used to synthesize nickel oxide nanoparticles (AgNPs) from silver nitrate and S. trilobatum leaf extract. According to X-ray diffraction (XRD) tests, the cubic phase was face-centered, had good crystallinity, and had average crystallite sizes. According to morphological studies, the surface has a cylindrical and rod-like morphology, and average particle size estimates from UV-visible spectroscopy (UV), Fourier transform infrared (FT-IR), concur well with XRD, and the bio-reduced silver nanoparticles were characterized. Staphylococcus aureus, Enterococcus faecalis, Streptococcus mutans, Pseudomonas aeruginosa, and the human pathogenic microorganisms were used to investigate the antibacterial efficacy (12.5, 25, 50 μg/mL) of these biologically created silver nanoparticles.